Stem cell therapies for COVID‐19: Strategy and application. Issue 12 (21st July 2020) - Darabi, Radbod; Li, Yong
Abstract: In this perspective, the potential application of stem cells for the treatment of COVID‐19 related pneumonia and their potential mechanism of action have been overviewed. Abstract : Stem cells can regulate the inflammation through the secretion of cytokines. They can also prevent tissue damage and participate in tissue repair. Stem cells are considered as one of the potential therapies for COVID‐19.